Hypoxia-induced immunosuppression in uveal melanoma is mediated by CD63+ exosomes delivering lactate to reprogram immune cells - Dong, Lei; Zheng, Suilian; Feng, Yixia (Frontiers in Molecular Biosciences, 2026)
Uveal melanoma (UM) is characterized by profound immunosuppression, resistance to immunotherapy, and significant hypoxia. This study investigates the role of hypoxia in mediating metabolic crosstalk with immune cells via CD63-enriched exosomes. Single-cell transcriptomic analysis identified a CD63-high tumor subpopulation in UM associated with lactate metabolism and vesicle transport. Under hypoxic conditions (1% O2 vs. 21% O2 normoxia), UMT2 cells exhibited upregulation of CD63 expression, increased exosome secretion, and elevated exosomal lactate levels. In co-culture assays, these hypoxic exosomes promoted macrophage M2 polarization, as indicated by increased CD206+ expression and elevated Extracellular Acidification Rate/Oxygen Consumption Rate (ECAR/OCR) ratios in macrophages and induced CD8+ T cell exhaustion, as evidenced by higher PD-1+TIM-3+ expression, and promoted the secretion of immunosuppressive cytokines such as TGF-β and IL-10. Importantly, these effects, which were driven by exosomal lactate transfer leading to macrophage metabolic reprogramming, were abolished upon CD63 knockdown using siRNA. Mechanistically, CD63 facilitates a hypoxia-induced exosomal lactate shuttle. We conclude that CD63-mediated transfer of hypoxic exosomal lactate establishes a critically immunosuppressive microenvironment in UM. Targeting the hypoxia/CD63/exosomal lactate axis may represent a promising novel therapeutic strategy to restore anti-tumor immunity in UM.